Microbiological Water Quality Disparities among Tribal and Non-tribal Farm Households in Assam, India - , Syeda Shabana Yasmin; , Bijoylaxmi Bhuyan; , Pradip Borah (Archives of Current Research International, 2025)
This study examines and compares potable water quality among tribal and non-tribal farm households in the Jorhat district of Assam. Despite similar socio-economic challenges, disparities exist in water access, usage practices, and microbiological safety.While water quality encompasses a range of parameters—chemical, physical, and heavy metal contamination—this study specifically focuses on microbiological aspects due to their direct implications for public health. Based on data from 100 farm households across four villages and microbiological analysis of 36 water samples, the study reveals that tube wells are the primary water source for both groups, yet inadequate treatment and unsafe storage practices persist. Notably, only 40% of tribal farm households covered their water containers, compared to 78% of non-tribal ones. Microbiological tests found bacterial counts exceeding safe limits, especially in filtered and raw water, while boiled water showed better results. These findings highlight the urgent need for improved rural water infrastructure, targeted hygiene education, and integration of water safety into housing and public health policies. Addressing these gaps is vital for reducing health risks and supporting the Sustainable Development Goals (SDG 6 and SDG 11).